Analysis of Contractile Function of Permeabilized Human Hypertrophic Cardiomyopathy Multicellular Heart Tissue - Kresin, Nico; Stücker, Sabrina; Krämer, Elisabeth; Flenner, Frederik; Mearini, Giulia; Münch, Julia; Patten, Monica; Redwood, Charles; Carrier, Lucie; Friedrich, Felix W. (Frontiers in Physiology, 2019)
Background. Many forms of hypertrophic cardiomyopathy (HCM) show an increased myofilament Ca2+ sensitivity. This observation has been mainly made in HCM mouse models, myofilament systems, and cardiomyocytes. Studies of multicellular tissues from patients with different HCM-associated gene mutations are scarce. We investigated Ca2+ sensitivity in multicellular cardiac muscle strips of HCM patients. We furthermore evaluated the use of epigallocatechin-3-gallate (EGCg), a Ca2+ desensitizer. Methods. After strip isolation from cardiac tissues with single (MYBPC3, MYH7) or double heterozygous mutations (MYBPC3/FLNC, MYH7/LAMP2, MYBPC3/MYH7) and permeabilization we performed contractility measurements ±EGCg. We furthermore evaluated gene expression with a customized heart failure gene panel using the NanoString technology. Results. Fmax tended to be higher in HCM than non-failing (NF) control strips and in single than in double heterozygous strips. Ca2+ sensitivity was higher by trend in most HCM vs. NF strips and by trend in tissues with double vs. single heterozygous mutations. EGCg desensitized myofilaments to Ca2+ in most of the strips and tended to induce a more pronounced shift in strips with truncating than missense or single than double heterozygous mutations. Gene expression analysis revealed lower ATP2A2, PPP1R1A, FHL2, and higher NPPA, NPPB, COL1A1, CTGF, POSTN marker levels in HCM than in NF tissues. NPPA, NPPB, ACTA1, CTGF, COL1A1, POSTN levels were higher in tissues with missense than truncating mutations. Conclusion. We report an increased myofilament Ca2+ sensitivity in native multicellular cardiac HCM strips, which by trend was more pronounced in samples with double heterozygous mutations. EGCg could have differential effects depending on the underlying genetic status (single vs. double heterozygous) and type (missense vs. truncating).